Incidence of ablation‐induced esophageal injury associated with high‐power short duration temperature‐controlled pulmonary vein isolation using a specialized open‐irrigated ablation catheter: A retrospective single‐center study. (23rd January 2021) - Piringer, Robert; Deneke, Thomas; Foldyna, Borek; Sonne, Kai; Nentwich, Karin; Ene, Elena; Barth, Sebastian; Lüsebrink, Ulrich; Berkovitz, Artur; Halbfass, Philipp
Abstract: Introduction: To evaluate short‐term efficacy and incidence of ablation‐induced endoscopically detected esophageal injury in patients undergoing high‐power, short‐duration (HPSD) pulmonary vein isolation using a novel irrigated radiofrequency ablation catheter and ablation generator setup. Methods and Results: Atrial fibrillation (AF) patients, who underwent AF ablation using an irrigated radiofrequency ablation catheter specifically designed for a HPSD ablation approach (50 W, with a target Ablation Index of 350 at posterior wall), received postablation esophageal endoscopy after ablation. In total 45 consecutive patients (67 ± 10 years; 58% male; 42% paroxysmal AF) undergoing AF ablation using a specialized ablation catheter (QDOT) were included in the study. Thirty‐one of 45 patients (69%) underwent a first‐time pulmonary vein isolation (Group 1, 67 ± 11 years; 55% male; 48% paroxysmal AF). Fourteen patients (31%) underwent a redo AF procedure (Group 2, 66 ± 8 years; 64% male; 29% paroxysmal AF). Patients undergoing first‐time pulmonary vein isolation were included in the final analysis. In these patients an endoscopically detected esophageal lesion (EDEL) was detected in 5 of 31 (16%) patients (erosion n  = 2, ulcer n  = 3). Mean contact force at posterior wall ablation sites was significantly lower in patients with postprocedural EDEL compared with patients without EDEL (11.9 ± 0.8 g vs. 15.6 ± 4.7 g). Conclusion: PVI using a specialized high‐power ablation catheter in conjunction with a HPSD ablation approach results in a 16% incidence of EDEL in first AF ablation candidates. Future studies evaluating high‐power short duration ablation strategies should include esophageal endoscopy to estimate the risk of clinically relevant esophageal complications.